Evaluation of the correlation between severity of acquired idiopathic generalized anhidrosis and quality of life scores. Issue 7 (22nd March 2017) - Munetsugu, Takichi; Fujimoto, Tomoko; Satoh, Takahiro; Nakazato, Yoshihiko; Ohshima, Yuichiro; Asahina, Masato; Yokozeki, Hiroo
Abstract: Symptoms of acquired idiopathic generalized anhidrosis (AIGA) include heat retention and/or heat stroke due to the effects of the disorder on the perspiration ability of the whole body under thermal environmental changes or exercise. Additionally, cholinergic urticaria can also occur in these patients. AIGA has a major impact on everyday life. However, the effects of AIGA severity on the quality of life (QOL) of the patients have not been sufficiently defined. The objective of this study was to evaluate the correlation between AIGA severity and QOL. Study subjects comprised 44 patients diagnosed with AIGA at three registered institutions. AIGA severity assessment was conducted and the Dermatology Life Quality Index (DLQI) questionnaire was administered. Correlations between AIGA severity and DLQI, as well as severity by DLQI subscale, were assessed. We found a positive correlation between total score of AIGA severity criteria and DLQI total scores ( R = 0.720, P = 0.001). The impairment increased with the increase in AIGA severity ( P < 0.01). In relation to the DLQI subscales, leisure (social and sporting activities) impairment was significantly higher for patients with severe AIGA than those with mild AIGA ( P < 0.01). Comparing QOL for AIGA patients with that of patients with other dermatological disorders, it is possible that QOL impairment for AIGA patients is as severe as that for patients with atopic dermatitis. AIGA severity and DLQI are correlated and AIGA patients experience disruption of everyday life more broadly than conventionally perceived.